Ernst Shaigardanovich Khaziakhmetov: scientist-researcher, teacher, person. 1936–2007 yy. - S. V. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
The interest in the formation and development of historical science in the region led to the need to create a socio-political history of the Siberian region. This goal is achieved in the second half of the 20th century thanks to the efforts of a number of researchers. Many of the researchers do history and social studies teachers trained as part of the transition to universal secondary education. One of them was E. Sh. Khaziakhmetov. Based on the memoirs of colleagues, reference materials and archival funds, personal impressions, the author comes to the conclusion that Doctor of Historical Sciences, Professor E. Sh. Khaziakhmetov is one of the founders of the scientific school for the study of pre-revolutionary political exile in Siberia. A man of his time: a child who lost his father and survived the war, a student during the «thaw», a witness to the development of the region in the post-war years and a university teacher. In what he saw the usefulness of his work, how his political views changed over the years, changes in the socio-economic system and political system, the presented material will tell.